The Use of Pictionary Games to Improve Seventh Grade Students’ Speaking Skill at SMP Negeri 5 Sukawati - I Made Handika Hendrayuda; Putu Santi Oktarina; Komang Trisna Dewi (Indo Publishing, 2026)
The objective of this study was to investigate the best implementation of Pictionary Games in improving seventh grade students’ speaking Skill at SMP Negeri 5 Sukawati. This research employed a Classroom Action Research (CAR) design that involves four stages in the cycle: planning, action, observation, and reflection. The research subjects in this study were 38 students consisting of 22 female and 16 male students in class VII H of SMP Negeri 5 Sukawati. The researcher used test and observation to collect the data. The data were analyzed by qualitative and quantitative data analysis. The results showed the use of Pictionary Game that integrated with Problem-Based Learning (PBL): 1) introducing the problem, 2) forming groups and planning learning, 3) exploring the problem, 4) presenting solutions or ideas, 5) reflecting and evaluation showed able to improved students’ speaking skill. Students’ speaking test were improved from 70,74 in preliminary research to 77,16 in Cycle 1 and 80,95 in Cycle 2. The results of the observation also showed that the learning process run in accordance of plans, students were very enthusiastic as observed from their active participation, and 100% (38 students) scored above the KKM (75). Therefore, the used of Pictionary Game able to improved students’ speaking skill.